42 The effect of Sheng Jiangsan on inflammatory factors in the allergic rhinitis rat model. (19th December 2016) - Wang, Ting; Wang, Fengjie; Wang, Baigen
Abstract : Objectives: To observe the effect of the traditional Chinese compound Sheng Jiangsan on the allergic rhinitis rat model. Methods: Male Wistar rats weighing 180–200 g were maintained under laboratory conditions for 3 days. Rat nasal smears were collected and proved negative for eosinophils. Once a day for 7 days, a pipette was used to administer 10 µL of olive oil solution containing 10% diisocyanate into the anterior nostrils (5 µL per nostril, two drops each). A rhinitis symptoms total score of >5 points and nasal secretions containing a large number of eosinophils indicated successful establishment of allergic rhinitis in rats. Every other day, each rat should be given two drops of diisocyanate olive oil solution to maintain sensitization until the end of the experiment. Results: Sheng Jiangsan administered for 14 consecutive days to the nasal cavity of rats with allergic rhinitis can significantly relieve the symptoms of allergic rhinitis (sneezing, nasal itching, runny nose, etc), reduce the rhinitis symptom total score and significantly decrease the eosinophil count in nasal secretions. Ling Shu nasal spray delivered to rats with allergic rhinitis significantly decreased serum IL-4 and IgE levels and significantly increased serum IFN-γ levels. Conclusions: The traditional Chinese compound Sheng Jiangsan can reduce rhinitis symptoms in the allergic rhinitis rat model, by reducing nasal secretions, inflammation and pathological changes in nasal mucosa.